Evaluation of urban highway environmental noise pollution - Sumiani Yusoff ,; Asila Ishak, (Universiti Kebangsaan Malaysia, 2005)
The increase in number of urban highways constructed around residential and community areas around the city, has inevitably caused major noise pollution problems to city dwellers. The objective of the study was to assess the level of noise exposure and its impact to residents residing around the vicinity of urban highways. Noise level recording was carried out at selected areas to determine the noise pollution levels and the adequacy of mitigating measures that has been implemented. Traffic volume along the highway was recorded and categorized into six major classes of vehicles. Subsequently, the Leq, L10, L50 and L90 noise index percentiles were identified and data analyses were done on the data samples. Simultaneously, a public survey was conducted to gauge the existing public's attitude and degree of awareness with contemporary motor vehicular noise pollution. The study revealed that the noise level exposure experienced by the residents exceed the DOE's guidelines on a daily basis whilst the measures taken was inadequate to curb the noise menace emitting from the neighboring urban highway.